PENTINGNYA KEPERCAYAAN DIRI DAN MOTIVASI SOSIAL DALAM KEAKTIFAN MENGIKUTI PROSES KEGIATAN BELAJAR - Fani Juliyanto Perdana (Department of Tadris IPS FITK IAIN Syekh Nurjati Cirebon, 2019)
Every human personality, confidence is an important indicator to produce success in relation to the activities that he does. However, there are things that cannot be denied that the level of confidence possessed by each individual is different, and al is influenced by other factors besides the process of maturity itself. A student's confidence in his activities when attending the KBM is not only influenced by motivation but also influenced by the ability in the knowledge he has. In the discussion in this research that is to help how to grow self-confidence for students in their activities when participating in the KBM process, how motivation for students studying in STIKes Cirebon. How is the influence of self confidence on motivation in activeness following the KBM process at STIKes Cirebon. The population in this study was to take samples at the first semester level I students of the STIKes Cirebon Public Health Study Program in 2018/2019 with a total of 23 students, this study was conducted using descriptive qualitative methods. Because this method is considered able to uncover, explore and analyze empirical phenomena that occur at the present time by describing or describing in accordance with the facts that occur from the results of the study.